‘‘Desarrollo de un Sistema de Indicadores de Sostenibilidad Ambiental para la Conservación de la Parroquia de San Miguel, Cantón Salcedo - Provincia de Cotopaxi’’ - Mora Clavijo, Francisco Javier (2024)
Nowadays, environmental challenges are one the main concerns, and the indicators implementation will contribute to establish policies, what promote environmental care. The main aim of this research project was to develop a environmental sustainability indicators system for the San Miguel parish, located in the Salcedo canton from Cotopaxi Province. It was made an information exhaustive collection to assess the environmental problems present in the parish, with the fundamental purpose by creating indicators, which will encompass social, environmental and economic aspects to ensure the natural resources appropriate use in the area. The used methodology included a qualitative phase, what is involved bibliographic review, geospatial description and interviews analysis conducted with 5 people, including housewives, public workers and community leaders from parish. These interviews and surveys provided detailed information about environmental problems and knowledge lack in the area. The results revealed, which 70.2% respondents identified poor solid waste management as the main environmental problem in the parish, while 52% pointed unemployment as the main concern in the social sphere. Furthermore, it was found that a population 13% lacks knowledge about recycling, which can have negative impacts on the environmental environment and the local inhabitants health. After identifying these problems, it proceeded to develop 40 environmental sustainability indicators, distributed in the social, environmental and economic spheres, with the aim by orienting the project towards sustainable development and improving the current situation from San Miguel these aspects, thus promoting sustainability and ecological balance.